Case Report: Simultaneous Resection of Bone Tumor and CAD/CAM Titanium Cranioplasty in Fronto-Orbital Region - Yashin, Konstantin S.; Ermolaev, Anton Yu.; Ostapyuk, Mikhail V.; Kutlaeva, Marina A.; Rasteryaeva, Marina V.; Mlyavykh, Sergey G.; Medyanik, Igor A. (Frontiers in Surgery, 2021)
Background. Simultaneous resection of bone tumors in the fronto-naso-orbital region is a significant challenge due to the need for adequate reconstruction of a facial skeleton. A preoperative virtual planning of resection margins and the simultaneous fabrication of the cranioplasty using computer-aided design/computer-aided manufacturing (CAD/CAM) technology could allow combining the tumor resection and cosmetic restoration steps into a single procedure. Methods. We present four consecutive cases of patients with bone tumors of fronto-naso-orbital region. The indications for surgery included: (1) the presence of a major cosmetic defect and (2) progressive tumor growth. The histological examination revealed vascular malformation, hemangioma, and fibrous dysplasia in two cases. Tumor resection was performed with the help of a drilling template in the form of a tumor. The computer-designed cranioplasty formed based on the noninvolved side of the patient's skull was manufactured. In one patient the reconstruction was performed using two separate implants. Results. The position of the implant fits in with preoperative planning in two cases, and in both of these cases, the additional trimming of the implant or bone defect was required. Good cosmetic outcomes were noted in all patients, and no complications occurred. No repeat surgery was necessary. The template has proven to have high application potential. Conclusion. Simultaneous resection and CAD/CAM cranioplasty in the case of bone tumors in the fronto-orbital region is a promising technique with the aim of minimizing operation time and achieving a good aesthetic outcome.